Dispensing of psychotropic drugs in the Brazilian capital city before and during the COVID-19 pandemic (2018–2020) - Escalante Saavedra, Pamela Alejandra; Galato, Dayani; de Souza Silva, Calliandra Maria; Rodrigues da Silva, Izabel Cristina; da Silva, Emília Vitoria (Frontiers in Pharmacology, 2022)
Objective. Evaluate data on the psychotropic drugs dispensed of psychotropic drugs by private community pharmacies before and during the SARS-CoV-2 pandemic. Methods. This cross-sectional study compared the quarterly and annual consumption per Defined Daily Dose per 1000 inhabitants-day (DHD) of psychotropic drugs. Interrupted time series were also constructed to expose changes in the consumption pattern in the periods before and after March 2020. Results. Among the 20 most consumed psychoactive drugs, 12 were antidepressants, escitalopram (DHD 7.996 and 10.626; p<0.001), and sertraline (DHD 6.321 and 8.484; p<0.001), in addition to the hypnotic zolpidem (DHD 6.202 and 8.526; p<0.001). The time series reveals (R2 value) a variation in drug dispensing, in DHD values, during the pandemic. Conclusion. Despite the higher variance, a significant increase is clearly seen in the consumption trends of psychoactive drugs, particularly antidepressants, consistent with the pandemic´s influence on the general population´s mental health.